On the correlation between discourse frequency and structural complexity in markedness theory - Regina Pustet (Discours)
Markedness is commonly regarded as one of the fundamental organizing principles of human language. However, the reasons for the existence of markedness phenomena continue to be controversial, if not to say obscure. The analysis of discourse corpora from three genetically unrelated languages which is conducted in this study suggests that at least one of the decisive aspects of markedness, namely, the correlation between frequency and structural complexity, can be understood as a necessary consequence of the general statistical regularities disclosed in Zipf's discourse-based model of language.